ESGO Survey on Current Practice in the Management of Cervical Cancer - Dostalek, Lukas; Åvall-Lundqvist, Elisabeth; Creutzberg, Carien L; Kurdiani, Dina; Ponce, Jordi; Dostalkova, Iva; Cibula, David (International journal of gynecological cancer, 2018)
OBJECTIVE: The aim of this survey was to acquire an overview of the current management of cervical cancer with an emphasis on the early disease stages. MATERIALS AND METHODS: A hyperlink to the survey was sent to the European Society of Gynaecological Oncology Office database. The survey contained 6 groups of questions regarding the characteristics of respondents, pretreatment workup, management of the early stages of cervical cancer, adjuvant treatment, fertility-sparing treatment, and surveillance. RESULTS: In total, 566 responses were collected. The most frequent imaging method used in the workup was magnetic resonance imaging (74%), followed by computed tomography (54%) and positron emission tomography/computed tomography (25%). Conization or simple hysterectomy was a preferred procedure in stage T1a1 lymphovascular space invasion (LVSI)-positive for 79% of respondents, in stage T1a2 LVSI-negative for 58%, and in stage T1a2 LVSI-positive for 28%. Sentinel lymph node biopsy alone was reported in stage T1a1 by 17% and in stage T1b1 less than 2 cm by 9%, whereas systematic lymphadenectomy by 29% and 90% of respondents. Macrometastases, micrometastases, and isolated tumor cells in lymph nodes were considered indications for adjuvant treatment by 96%, 93%, and 68% of respondents, respectively. Neoadjuvant chemotherapy was reported by 28% and 19% of respondents in fertility-sparing and nonsparing management in stage T1b1. Over 60% of respondents recommend primary surgery for their patients with T1b2 N0 disease and 81% of them use a combination of adverse prognostic factors as indication for adjuvant radiotherapy in pN0 disease. CONCLUSIONS: The results of this survey indicate considerable differences in the workup and treatment of cervical cancer in current clinical practice.
Keywords: dospělí; Magnetic Resonance Imaging; průzkumy a dotazníky; Female; Adult; ženské pohlaví; Surveys and Questionnaires; lymfatické uzliny; lidé; staging nádorů; magnetická rezonanční tomografie; nádory děložního čípku; Lymph Nodes; Uterine Cervical Neoplasms; lidé středního věku; zachování plodnosti; Middle Aged; Neoplasm Staging; Fertility Preservation; Humans